Corporate Social Responsibility Berbasis Islamic Social Reporting Index - Nurlailah; Nurul Fitri Ismayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study is designed to examine Corporate Social Responsibility within Shariah-compliant banking institutions. based on the Islamic Social Reporting (IISR) index. This research analyzed the content of annual reports issued by Islamic commercial banks in Indonesia. Thirteen Islamic commercial banks registered with the Financial Services Authority in 2024 served as the objects of this study The research utilized the content analysis approach, where CSR reports of Sharia-compliant commercial banks were analyzed by the researcher in accordance with the IISR. Based on secondary data obtained from each bank's website, namely the annual financial reports of Sharia-compliant commercial banks in 2024. The conclusions drawn from this study indicate that Bank Muamalat Indonesia has the highest disclosure percentage with 74%, while Bank Victoria Syariah has the lowest disclosure percentage with a percentage of 16%. The study explores the level of CSR with the Islamic Social Reporting Index in 13 Sharia-compliant commercial banks based on the 2024 annual reports. The conclusions of this study may be employed to determine how Islamic commercial banks report their social funds.